The Effect of Serum Origin on Tissue Engineered Skeletal Muscle Function. Issue 12 (15th October 2014) - Khodabukus, Alastair; Baar, Keith
ABSTRACT Skeletal muscle phenotype is regulated by a complex interaction between genetic, hormonal, and electrical inputs. However, because of the interrelatedness of these factors in vivo it is difficult to determine the importance of one over the other. Over the last 5 years, we have engineered skeletal muscles in the European Union (EU) and the United States (US) using the same clone of C2C12 cells. Strikingly, the dynamics of contraction of the muscles was dramatically different. Therefore, in this study we sought to determine whether the hormonal milieu (source of fetal bovine serum (FBS)) could alter engineered muscle phenotype. In muscles engineered in serum of US origin time‐to‐peak tension (2.2‐fold), half relaxation (2.6‐fold), and fatigue resistance (improved 25%) all showed indications of a shift towards a slower phenotype. Even though there was a dramatic shift in the rate of contraction, myosin heavy chain expression was the same. The contraction speed was instead related to a shift in calcium release/sensitivity proteins (DHPR = 3.1‐fold lower, slow CSQ = 3.4‐fold higher, and slow TnT = 2.4‐fold higher) and calcium uptake proteins (slow SERCA = 1.7‐fold higher and parvalbumin = 41‐fold lower). These shifts in calcium dynamics were accompanied by a partial shift in metabolic enzymes, but could not be explained by purported regulators of muscle phenotype. These data suggest that hormonal differences in serum of USDA and EU origin cause a shift in calcium handling resulting in a dramatic change in engineered muscle function. J. Cell. Biochem. 115: 2198–2207, 2014. © 2014 Wiley Periodicals, Inc.